Capacity to Consent for Treatment in Patients with Psychotic Disorder: A Cross-Sectional Study from North Karnataka. Issue 6 (November 2022) - Grover, Druhin; Tekkalaki, Bheemsain; Yadawad, Vishwas; Patil, Nanasaheb M.; Chate, Sameeran S.; Patil, Sandeep
Background: Recently, the Mental Healthcare Act (MHCA) 2017 was introduced in India. Being a right-based act, it has made the assessment of the capacity to consent an integral part of clinical work. To the best of our knowledge, there are no Indian studies on this topic. Hence, this study aimed to assess the capacity to consent to mental healthcare and treatment in patients with functional psychosis and the factors affecting the same. Methods: This cross-sectional study included participants with the ICD-10 DCR diagnosis of a psychotic disorder admitted in the psychiatry ward of a tertiary health care center in Karnataka, India. MacArthur Competence Assessment Tool for Treatment was used to assess the capacity to consent to treatment. Brief Psychiatric Rating Scale (BPRS) and the Beck Cognitive Insight Scale were applied to assess the severity of psychosis and level of insight, respectively. Results: A hundred participants were recruited. Twenty-four were found to have an intact capacity to consent to treatment. High BPRS scores (P value = 0.0002) and low insight scores (P value = 0.0002) were associated with an impaired capacity. Conclusion: About one-fourth of participants had an intact capacity to consent to treatment. Higher severity of psychosis and a poorer insight into the illness were associated with impaired capacity to consent.